Respuesta :

To find the inverse of this function, we first need to replace f(x) with y.

y = 2x^2 + 3

Now, we swap x and y

x = 2y^2 + 3

Now, we solve for y.

-3

x - 3 = 2y^2

Sqrt both sides.

√(x - 3) = 2y

Divide by 2

√(x - 3)/2 = y

Replace y with f^-1(x)

√(x - 3)/2 = f^-1(x)


Just realized you were asking for f(-1), not f^-1(x)

Feels bad.

f(-1) = 2(-1^2 + 3)

f(-1) = 2(-1^5)

f(-1) = 2(-1)

f(-1) = -2

I'm leaving the original answer in case you also need the inverse function. :)

ACCESS MORE